KEPASTIAN HUKUM PENERAPAN JUSTICE COLLABORATOR TERHADAP PELAKU TINDAK PIDANA NARKOTIKA. - Pratama, Dimas Satriawan Syah; Chandra, Tofik Yanuar; Ismed, Mohamad (LPPM Institut Pendidikan Nusantara Global, 2024)
The idea of a Justice Collaborator is based on Article 37 paragraph (2) of the 2003 United Nations Convention Against Corruption (UNCAC) which states that the state is obliged to consider reducing the sentence of perpetrators who provide substantial cooperation in the investigation and prosecution of a specified crime. As of 2023, UNCAC has 190 member countries which have proven that the article regarding Justice Collaborator is an effective way to eradicate organized crime such as narcotics. The Research method is a normative juridical research, to obtain the necessary data in connection to the period issue. The data used is secondary data in consisting of primary legal materials. Besides, it used primary data to support secondary data legal materials. Data analysis was done by qualitative juridical analysis. The result of research is obtained that From the research results, it can be seen that Justice Collaborator is a form of symbiotic mutualism or mutually beneficial cooperation between Witnesses and Perpetrators of law enforcement officers where each of them gets benefits related to the disclosure of narcotics crime cases. The legal basis for Justice Collaborator began with the publication of SEMA No. 4 of 2011, Joint Regulations, to Law no. 31 of 2014. In the PSK Law, the position of Justice Collaborator is regulated as equal to Witness, Victim and Whistleblower and their rights are guaranteed by law, but in practice there are still many perpetrator witnesses who do not get leniency because in the trial the judge does not consider the testimony of the perpetrator witness to meet the requirements. as Justice Collaborator. Even though the legal basis already exists, because in the Indonesian judicial system the decision maker is the judge, the recommendation of the prosecutor or LPSK does not necessarily lighten the sentence of the perpetrator witness